2016
DOI: 10.1016/j.sjbs.2015.09.022
|View full text |Cite
|
Sign up to set email alerts
|

In vitro importance of probiotic Lactobacillus plantarum related to medical field

Abstract: Lactobacillus plantarum is a Gram positive lactic acid bacterium commonly found in fermented food and in the gastro intestinal tract and is commonly used in the food industry as a potential starter probiotic. Recently, the consumption of food together with probiotics has tremendously increased. Among the lactic acid bacteria, L. plantarum attracted many researchers because of its wide applications in the medical field with antioxidant, anticancer, anti-inflammatory, antiproliferative, anti-obesity and antidiab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 34 publications
1
47
0
Order By: Relevance
“…This led us suppose that the change of intestinal flora artificially may have some effects on high‐fat diet rat. Studies showed that LP has some effects in regulating humoral immunity and cholesterol‐lowering effects (Ushakova et al ., ; Yoo et al ., ; Arasu et al ., ), while LF has lipid‐lowing function and can alter the intestinal microflora (Tomaro‐Duchesneau et al ., ; Liu et al ., ). So it is our purpose to use these two strains in combination to study their effects on high‐fat diet rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This led us suppose that the change of intestinal flora artificially may have some effects on high‐fat diet rat. Studies showed that LP has some effects in regulating humoral immunity and cholesterol‐lowering effects (Ushakova et al ., ; Yoo et al ., ; Arasu et al ., ), while LF has lipid‐lowing function and can alter the intestinal microflora (Tomaro‐Duchesneau et al ., ; Liu et al ., ). So it is our purpose to use these two strains in combination to study their effects on high‐fat diet rats.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus Plantarum (LP) has been studied extensively for its antioxidation, anticancer, antiobesity, etc. Therefore, this strain has been used extensively (Costilow & Humphreys, 1955;Yoo et al, 2013;Arasu et al, 2016). Lactobacillus fermentum (LF) has also been used to alter the intestinal flora and thus showing its healthy effects (Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The growth pattern of the strain was measured intermittently, and extracellular metabolites, such as acetic acid, succinic acid, lactic acid, and ethanol, were quantified by HPLC. 16,17 Cultivation and purification of antimicrobial components The initial antimicrobial screening results confirmed that the Lactobacillus strain D-3 exhibited promising activity with stability for a wide range of hydrolytic enzymes, acids, and organic solvents. 18 Therefore, after cultivation, the supernatant was mixed with different organic solvents, such as hexane, chloroform, ethyl acetate, and methanol, to improve antimicrobial component yields.…”
Section: Organic Acid Profiling Of Extracellular Productsmentioning
confidence: 94%
“…Similarly, the metabolite production ability of the strains using date syrup was also investigated. The growth pattern of the strain was measured intermittently, and extracellular metabolites, such as acetic acid, succinic acid, lactic acid, and ethanol, were quantified by HPLC …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation